A Representation of Douseikon in the Film Boku mo Aitsu mo Shinro desu: A Study on Same-Sex Marriage and Cultural Conflict in Contemporary Japanese Cinema - Oktaviasari, Anisa; Yuana, Cuk (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study discusses the representation of same-sex marriage (referred to in Japanese as douseikon) in the film Boku mo Aitsu mo Shinro desu directed by Koji Tanaka. The film places the issue of homosexuality within the domestic sphere, particularly the home and family. The aim of this study is to analyze how the film negotiates personal issues with collective interests as a response to the evolving social diversity in contemporary Japanese society. This research employs a film analysis approach, focusing on the main characters, dialogues, and visual elements such as mise-en-scène and symbolic representations to examine the phenomenon of same-sex marriage. The method used is descriptive qualitative film analysis. The findings show that through this film, the main characters Aikawa Mizuki and Seto Ryosuke, strive for acknowledgment of their relationship amid familial and societal pressure. Through selected key scenes, the film illustrates the tension between individual desire and the constraints of dominant cultural values. Ultimately, the film not only gives voice to the issue of douseikon, but also reflects the ongoing negotiation of identity in a society. Keywords: Representation, Douseikon, Film, Identity, Homosexuality